Sequential coagulation/flocculation and microwave-persulfate processes for landfill leachate treatment: Assessment of bio-toxicity, effect of pretreatment and cost-analysis. (15th February 2019) - Tripathy, Binay Kumar; Kumar, Mathava
Graphical abstract: Highlights: Leachate treatment by coupled microwave-persulfate (MW-PS) system was investigated. COD removal of 67% and ammonia removal of 93% were observed in MW-PS system. The COD removal rate constant increased with increase in PS dosage in MW-PS system. Maximum COD removal was achieved at 20 g/L PS dosage and 500 W MW power. Cost and toxicity analysis were used to check suitability of MW coupled systems. Abstract: The possibility of landfill leachate treatment in a coupled microwave-persulfate (MW-PS) system with and without pretreatment, i.e. coagulation-flocculation (C-F) was investigated. The C-F pretreatment with alum and FeCl3 has reduced the turbidity from 90 NTU to 43 NTU and 10 NTU, respectively, at the optimized coagulant dosage. Moreover, 73% COD and 86% color removal was observed in C-F pretreatment with FeCl3 . The application of MW-PS system (at 10 g/L of PS dosage) for pretreated leachate (FeCl3 dosage 1 g/L and pH 5.5) has produced a final COD removal of 89%. Similarly, alum pretreatment (dosage 1.6 g/L, pH 8.2) coupled with MW-PS system has achieved a total COD removal of 62%. In MW-PS system, the ratio of initial PS dosage to initial COD ratio has shown significant effect on leachate treatment. However, slightly lesser ammonia removal was observed in MW-PS (93%) compared to MW alone (97%) owing to reduction in pH of the system. The comparison of bio-toxicity (i.e. inhibition to aliivibrio fischeri) of treated samples from MW-PS and MW alone after pretreatment, i.e. 12.1 mg/L and 6.8 mg/L of equivalent ZnSO4 toxicity, indicated that MW-PS treated sample were found to be more toxic than MW alone treatment and raw leachate (7.6 mg/L and 7.2 mg/L of equivalent ZnSO4 toxicity, respectively) due to sulfate ion. This indicates that C-F followed by MW alone would be an ideal option for leachate treatment. The cost and energy estimation of MW and MW coupled systems well supported the above findings.